Accountability and the restraint of freedom: A deontological case for the stricter standard of corporate disclosure - Brummer, James J. (Journal of business ethics, 1986)
The purpose of the article is to give a deontological defense of the reasonableness standard of corporate disclosure presently mandated by the Securities and Exchange Commission of the U.S. government. The first part of the article distinguishes the reasonableness standard from the older standard of materiality. The second part presents three deontological arguments, inspired by the work of Ross and Kant, for the prima facie compellingness of the new standard.